2020
DOI: 10.1089/dna.2020.5614
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Mitochondrial DNA Variants and Mitochondria/Endoplasmic Reticulum Contact Sites: A Perspective Review

Abstract: Mitochondria contain their own genome, mitochondrial DNA (mtDNA), essential to support their fundamental intracellular role in ATP production and other key metabolic and homeostatic pathways. Mitochondria are highly dynamic organelles that communicate with all the other cellular compartments, through sites of high physical proximity. Among all, their crosstalk with the endoplasmic reticulum (ER) appears particularly important as its derangement is tightly implicated with several human disorders. Population-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Indeed, it has been recently shown that livers from obese mice are characterized by overexpression of phosphofurin acidic cluster sorting protein (PACS2) and IP3R and by enhanced Ca 2+ -related MERCs function, and that insulin sensitivity can be ameliorated upon downregulation of these two proteins [52,54]. Although apparently contradictory, these results could be explained by the use of different experimental models (e.g., likely with different genetic background, potentially also impacting MERCs [55]) and by the fact that the analysis was performed in tissues with different metabolic requirements. In any case, these lines of evidence highlight the fact that interaction between the ER and mitochondria contributes to insulin and/or glucose signaling in liver and insulin-sensitive peripheral tissues.…”
Section: Mercs and Metabolic Disordersmentioning
confidence: 99%
“…Indeed, it has been recently shown that livers from obese mice are characterized by overexpression of phosphofurin acidic cluster sorting protein (PACS2) and IP3R and by enhanced Ca 2+ -related MERCs function, and that insulin sensitivity can be ameliorated upon downregulation of these two proteins [52,54]. Although apparently contradictory, these results could be explained by the use of different experimental models (e.g., likely with different genetic background, potentially also impacting MERCs [55]) and by the fact that the analysis was performed in tissues with different metabolic requirements. In any case, these lines of evidence highlight the fact that interaction between the ER and mitochondria contributes to insulin and/or glucose signaling in liver and insulin-sensitive peripheral tissues.…”
Section: Mercs and Metabolic Disordersmentioning
confidence: 99%
“…Notably, in those disorders, altered MAM was associated with impaired bioenergetic output [ 17 , 18 , 54 ]. However, there is almost no information on the opposite possibility, namely, whether perturbed bioenergetics can affect MAM function [ 20 , 55 ]. We now show that, in fact, cells with deficiencies in OxPhos show perturbed MAM functions, but surprisingly, not in a uniform way.…”
Section: Discussionmentioning
confidence: 99%